THE INFLUENCE OF JAPANESE MODERN CULTURE VALUE TOWARD PURCHASE DECISION MAKING PROCESS ON YOUTH SOCIETY IN MANADO - Ngurawan, Ahmad Maulana; Pangemanan, Sifrid S.; Tielung, Maria V.J. (Universitas Sam Ratulangi, 2016)
The Japanese trending of new way on the modern culture now affects many aspects all around the country. From the technology aspect, film industry, music and also in fashion with odd ways. In Indonesia we are getting support by everything by in daily life, for example, in transportation, there so many Japanese products in automotive. Also, the aspect of new modern culture also is happening in Indonesia like otaku, anime, manga, and cosplay. Many incoming events helds in Indonesia from local scale to international scale influence young people. The event make more people interested with the Japanes. In Manado, the Japanese modernÂ culture impact on the young generation can be seen from many events that are held many times, as the main visitors in the Japanese modern culture event in. However parents also play important role in young generation involvement in Japanese modern culture events or to know more the Japanese modern culture are the parents cooperative enough to let them child to influence with it. Many young people follow the latest trend of Japanese culture example like the Fashion.The result of this research is that the Japanese modern culture is not significant with one possible reason is that not all of them have proper job to support their hobby in Japanese modern culture. The indicator related to parental controlling on the youth. Influence in decision making purchasing process in youth society in Manado. Keywords: modern culture, youth, decision making, market, consumer behaviour